Heavy Metal Islam Rock, Resistance, and the Struggle for the Soul of Islam. - LeVine, Mark (University of California Press, 2022)
This updated reissue of Mark LeVine's acclaimed, revolutionary book on sub- and countercultural music in the Middle East brings this groundbreaking portrait of the region's youth cultures to a new generation. Featuring a new preface by the author in conversation with the band The Kominas about the problematic connections between extreme music and Islam. An eighteen-year-old Moroccan who loves Black Sabbath. A twenty-two-year-old rapper from the Gaza Strip. A young Lebanese singer who quotes Bob Marley's ""Redemption Song."" Heavy metal, punk, hip-hop, and reggae are each the music of protest,